Poplar Rate Strike, 1921 (1921)
1921 1918-1939 "Poplar Rate Strike, 1921" [T0280.jpg], 1921 In March 1921, faced with a massive increase in the rate, the Council refused to cut the level of relief to the poor and withheld £270,000 in contributions required by the London County Council (LCC) until the wealthy West End boroughs took a fairer share. The council ignored a court order to pay, and in September the majority, led by George Lansbury were sent to prison. Faced with a threatened rent strike and enormous popular support for the councillors, the LCC and the Government eventually gave way and the High Court released them in October.